Ferulic Acid Combined With Bone Marrow Mesenchymal Stem Cells Attenuates the Activation of Hepatic Stellate Cells and Alleviates Liver Fibrosis - Zhang, Rui; Li, Wenhang; Jiang, Xiaodan; Cui, Xinyi; You, Hongjie; Tang, Zuoqing; Liu, Wenlan (Frontiers in Pharmacology, 2022)
Bone marrow mesenchymal stem cells (BMSCs) are effective in alleviating liver fibrosis, but the efficacy of cell therapy alone is not stable. In recent years, more people choose the combination of traditional Chinese medicine (TCM) and cell therapy to treat diseases in clinical trials. While, ferulic acid (FA) was highly effective in treating liver fibrosis, and the combination of cells and drugs is being experimented in clinical trials. Therefore, we combined BMSCs and FA to treat CCl4-induced fibrosis models to verify whether it showed better effective. We used BMSCs and FA to treat CCl4-induced fibrosis rat models and observed their therapeutic effect, investigated the specific mechanism of this combination therapy in liver fibrosis. We created a BMSC/hepatic stellate cell (HSC) co-culture system and used FA to treat activated HSCs to verify the specific mechanism. We next used cytochalasin D and angiotensin II to investigate whether BMSCs and FA inactivate HSCs through cytoskeletal rearrangement. MiR-19b-3p was enriched in BMSCs and targeted TGF-β receptor II (TGF-βR2). We transfected miR-19b-3p into HSCs and BMSCs separately and detected HSCs activation. We found that the expression of the profibrotic markers α-SMA and COL1-A1 was significantly decreased in the combination group of rats’ models. α-SMA and COL1-A1 were also significantly decreased in HSCs co-cultured with combination treatment. Cytoskeletal rearrangement of HSCs was inhibited in combination group, and RhoA/ROCK pathway gene expression was decreased. With angiotensin II treatment, COL1-A1 and a-SMA expression increased, while with cytochalasin D treatment, profibrotic gene expression decreased in HSCs. COL1-A1, α-SMA and RhoA/ROCK pathway genes were decreased in activated HSCs treated with a miR-19b-3p mimic, indicating that miR-19b-3p inactivated HSCs by suppressing RhoA/ROCK signaling. In contrast, profibrotic genes were significantly decreased in BMSCs treated with the miR-19b-3p mimic and FA or a miR-19b-3p inhibitor and FA compared with BMSCs treated with the miR-19b-3p mimic alone. In conclusion, the combination therapy had better effects than FA or BMSCs alone. BMSCs and FA treatment attenuated HSC activation and liver fibrosis by inhibiting cytoskeletal rearrangement and delivering miR-19b-3p to activated HSCs, inactivating RhoA/ROCK signaling. FA-based combination therapy showed better inhibitory effects on HSC activation.